Association between right ventricular dysfunction and appropriate icd therapy. (19th May 2022) - Chiba, T; Kajiyama, T; Yutaka, Y; Ryuzaki, S; Sugawara, M; Kitagawa, M; Ito, R; Nakano, M; Nakano, M; Kondo, Y; Kobayashi, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Right ventricular fractional area change (RVFAC) as right ventricular function is recently referred as an independent predictor of sudden cardiac death (SCD). The purpose of this study was to evaluate the association of RVFAC and appropriate ICD therapy in order to determine the cut-off value of RVFAC. Methods: Consecutive patients who underwent initial ICD implantation for any diseases except for non-dilated phase hypertrophic cardiomyopathy and channelopathy were retrospectively enrolled from 2012 to 2018. Primary endpoint was an initial appropriate ICD therapy. Transthoracic echocardiographic parameters before ICD implantation were evaluated by one physician and one echocardiologist to be validated. Right ventricular dimensions and function were also measured to be analyzed. Results: In total, 172 patients (60.3±13.6 years, 131 males) including 63 ischemic cardiomyopathy were enrolled. Ninety patients received an ICD as a secondary prophylaxis. Mean LVEF and RVFAC were 38.3±14.3% and 35.8±8.82%, respectively. There was little correlation between RVFAC and LVEF (correlation coefficient =0.274). Regarding appropriate ICD therapy events, the best cut-off value of RVFAC was 34.8%. The odds ratio of low RVFAC was 2.731 (95%CI: 1.456-5.121, P=0.00174). Secondary prophylactic cohort with low RVFAC showed highest incidence of appropriate ICD therapy as shown in the figure. In multivariate analysis, only low RVFAC is an independent predictor of appropriate ICD therapy (HR: 3.53, 95%CI:1.78- 6.99, P=0.0003). Conclusion: Low RVFAC seemed independently associated with increased appropriate ICD therapy.